2017
DOI: 10.1371/journal.pone.0174610
|View full text |Cite
|
Sign up to set email alerts
|

Night-time lights: A global, long term look at links to socio-economic trends

Abstract: We use a parallelized spatial analytics platform to process the twenty-one year totality of the longest-running time series of night-time lights data—the Defense Meteorological Satellite Program (DMSP) dataset—surpassing the narrower scope of prior studies to assess changes in area lit of countries globally. Doing so allows a retrospective look at the global, long-term relationships between night-time lights and a series of socio-economic indicators. We find the strongest correlations with electricity consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…The elasticity between luminosity and electricity consumption is between 0.9 and 1.1, as reported by Proville et al (2017) and the original work of Elvidge et al (1997). This suggests that a 1% drop in luminosity corresponds to a similar 1% drop in electricity consumption.…”
Section: Figsupporting
confidence: 69%
“…The elasticity between luminosity and electricity consumption is between 0.9 and 1.1, as reported by Proville et al (2017) and the original work of Elvidge et al (1997). This suggests that a 1% drop in luminosity corresponds to a similar 1% drop in electricity consumption.…”
Section: Figsupporting
confidence: 69%
“…Nightlight images give an opportunity to compare changes in night light intensity, which relates to electricity availability, for before and after a disaster. It has been shown that a strong correlation exists between night light intensity and GDP [112,113]. Furthermore, it has also been suggested as a potential proxy for economic resilience assessment [114].…”
Section: Macro Regional and Urban Economicsmentioning
confidence: 99%
“…The nightlight satellite data can measure several aspects of the city. First, nightlight satellite data can measure socioeconomic developments, such as gross domestic product [25][26][27][28], carbon emission [25,[29][30][31], electricity consumption [32][33][34][35], house vacancy [36], and population study [37][38][39]. Second, nightlight satellite data can measure urban areas in cities.…”
Section: Edges Measured By Nightlight Satellite Datamentioning
confidence: 99%
“…Relationship between areas with composite edges, representing a combined set of all edges related to social and physical features, and crime remains untouched in the literature. Nightlight satellite data, reflection of combined effect of socioeconomic developments [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and urban constructions [40][41][42][43][44][45][46][47][48][49][50][51], could be a suitable source to measure such composite edges. This study aims to explore the possible impact of composite edges measured by nightlight gradients on street robbery and burglary.…”
Section: Introductionmentioning
confidence: 99%